ANALISIS PERKEMBANGAN SEKTOR KEUANGAN TERHADAP PERTUMBUHAN EKONOMI DI NEGARA ISLAM - Izzun Khoirun Nissa (MAMBA'UL 'ULUM, 2021)
This study analyzes the development of the financial sector on economic growth in Islamic countries in twelve Islamic countries for the period of 2011-2018. This study aims to determine the effect of the sector from conventional and sharia banking or the whole on economic growth in Islamic countries and from the Islamic finance sector to economic growth in Islamic countries. This study applied panel data to estimate empirically involving 12 Islamic countries during the 2011-2018 period. This study reveals that the fixed Effect model is the best model to explain the effect of the independent variables as a whole and specifically the Islamic finance sector on the dependent variable. Overall, the results of this study indicate that the variables of interest rates, total assets of conventional banks, financing and total assets of Islamic banks have no effect on economic growth. Meanwhile, the deposit variable has a negative effect and the number of Islamic banks has a positive effect on economic growth. Furthermore, the test for the Islamic finance sector on economic growth, the financing variable and the number of sharia offices have a significant positive effect on economic growth. For the variable total assets of Islamic banks has no effect on economic growth.